Physical Growth of Sasak Children at Different Altitudes in Lombok Island - NOVITA TRI ARTININGRUM; BAMBANG SURYOBROTO; TETRI WIDIYANI (Bogor Agricultural University, Indonesia, 2014)
The physical growth that occurs in schoolage children is makes this period one of the most important phases in the human life cycle. Within this period, puberty is indicated by growth spurts that increase both stature (BH) and bodyweight (BW). The focus of this research is to evaluate the age-related body size variation in Sasak children living at different altitudes on the island of Lombok, Indonesia: low, medium, and high. Our results showed that children living at low altitude were taller and heavier than children of the same age living at medium and high altitudes. Up until the onset of puberty, the children at medium altitude have similar stature and weight to those residing at high altitude, but they are shorter and lighter thereafter. There were significant differences in the height and weight of girls in different altitude locations, but no significant difference for boys. The effect of SES on child growth can be comparison between Sasak and other populations in Indonesia. In general, the Sasak children are shorter and lighter than children of the same age in urban populations, and relatively similar in size to the children in rural populations. Indicators of socioeconomic status such as family income and parental education were shown to be more influential factors in the differentiation of physical growth between populations than the altitude factor